Cross-border cooperation as a tool for enhancing the international competitiveness of tourism destinations. A case study of the Murmansk region in northwest Russia as a part of the Barents tourism cluster - Saltykov, Maxim (UiT The Arctic University of Norway, 2015)
Establishing the multinational tourism cluster in the Barents region should be aimed at achieving sustainable and mutual profits for all participants through their cross-border cooperation on the global arena. The analysis of the competitive profile of the Murmansk region based on secondary sources and a qualitative research among its stakeholders confirms that it would be profitable for the destination to cooperate with its neighbors on tourist flows to the European Arctic. Benchmarking of the nature-based resources in the Barents region reveals that they can be marketed under a joint tourism brand. The differences in cultural heritages between Russia and its neighbors would add value to the cross-border products and could be perceived by international visitors as unique selling points. Coopetition in tourism in the European Arctic could be built around joint marketing and cross-border product development. Actions in this direction could result in enhancing destination’s international competitiveness through increasing awareness about it among the tourists and improving its overall performance. It could facilitate realization of the potential of the Barents region by creating cross-border products that consist of the tourist experiences in frontier areas. Though there are many challenges, the tourism stakeholders in the Murmansk region are positive about collaboration on international marketing and development of cross-border packages. The incorporation of the region into a tourism cluster in the European Arctic requires networking; an audit of the destination, and development of the cooperation model suited to all stakeholders in the Barents region.